Bacterial Agents and Their Antibiotic Susceptibility in Urinary Tract Infection (UTI) of Pediatric Age Group - Syed Muneeb Mohammad,Javid Ahmad,Nazir Ahmad Parray, Mohd Rafiq Lone*,Nisar Ahmad Ganie,Mohsin Rashid (Innovative Journal of Medical and Health Sciences, 2019)
Background: Urinary tract infections (UTIs) account for one of the common cause of hospital visits and therefore determination of the antimicrobial susceptibility patterns of uropathogens will help guide physicians to choice the best choice of antibiotics to affected patients. The aim of this study was to isolate the bacteriological agent causing the urinary tract infection and determination of their susceptibility to antibiotics. Methods: Our study was hospital based prospective study in which patients suspected of UTI were admitted and urine sample were collected using ‘urinary catheter’ method in patients less than 3 years of age, while for older children ‘mid stream clean catch’ method was used. Cultures were bacteriologically analyzed using standard microbiological procedures and antimicrobial susceptibility test was performed for the isolated pathogens. Results: 208 patients with suspected UTI were included in study, out of 208 patients, urine cultures were taken from all patients, 38 cultures (18.2%) were reported as positive. The most common pathogens isolated were Escherichia coli 27 (71%), Klebsiella Species 6 (15%), Enterococcussps 3(7.8%), Proteus sps 1(2.6%), Pseudomonas aeruginosa 1(2.6%). E. coli and Klebsiella showed the highest percentage of resistance to amoxicillin and ampicillin (100%) however, all isolates of E. coli and Klebsiella were susceptible to Nitofurantoin. Among all UTI isolates, least resistance was observed against drugs such as ceftriaxone, cefixime ciproflaxacilin and gentamicin. Conclusion: The finding of our study showed that E. Coli was the most common uropathogen and there was high resistance to routinely used drugs in clinical practice. So it high time to change the empirical therapy from conventional drugs like ampicillin and amoxicillin to drugs like nitrofurantoin or ciprofloxacilin. Keywords: Urinary tract infection, urine culture, antibiotic susceptibility.